2014
DOI: 10.2174/1874306401408010101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inhaled Corticosteroids on Glycemic Status

Abstract: Although the dysglycemic effects of systemic glucocorticoid therapy are well known, the effect of inhaled corticosteroids (ICS) on carbohydrate metabolism is still a subject of debate. The systemic bioavailability of ICS is claimed to be minimal and the side effects negligible. However, some large retrospective cohort studies showed a definite association between ICS use and incident diabetes or worsening glycemic control in pre-existing diabetes. There are no professional-body recommended guidelines on the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 46 publications
2
18
1
Order By: Relevance
“…However, we cannot reject that there may exist a causal pathway between asthma and development of type 1 diabetes, perhaps mediated via inhaled corticosteroid therapy. 29 In parallel with our findings, other studies have not been able to detect differences in asthma risk after previous type 1 diabetes diagnosis. 12 Some have, however, shown an increased subsequent risk of asthma, 4,6 which could result from surveillance bias.…”
Section: Discussionsupporting
confidence: 90%
“…However, we cannot reject that there may exist a causal pathway between asthma and development of type 1 diabetes, perhaps mediated via inhaled corticosteroid therapy. 29 In parallel with our findings, other studies have not been able to detect differences in asthma risk after previous type 1 diabetes diagnosis. 12 Some have, however, shown an increased subsequent risk of asthma, 4,6 which could result from surveillance bias.…”
Section: Discussionsupporting
confidence: 90%
“…Yucel et al found no effect of dose of inhaled corticosteroid and HbA1c value likewise in the current study there were no signi cant effects of dose of inhaled uticasone use on fasting plasma glucose, 2hour plasma glucose after 75 gm oral glucose and HbA1c% in the study group [8]. Some studies found dose dependent alteration of plasma glucose level although the subjects were diabetic [5,11,21].…”
Section: Discussionsupporting
confidence: 42%
“…Use of ICS in asthma for prolonged period and or higher dose has worsening effects on glycaemic status [7,8,9,10]. Several studies were done on the adverse effects of ICS revealing inconsistent ndings on glycaemic status of ICS users [11]. Therefore, this study was conducted on asthma patients to observe the glycaemic effect of inhaled uticasone users in Dhaka, Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Oral steroids could therefore have a significant impact upon the T2DM risk in asthma patients. There are mixed data relating to the effect of inhaled corticosteroids, which are prescribed for the vast majority of patients with asthma on diabetes incidence, although they may worsen glycaemic control in those with established diabetes [33]. Inhaled corticosteroid prescription was not assessed in any of the included studies.…”
Section: Confounding Factorsmentioning
confidence: 99%